2018
DOI: 10.1136/bmjopen-2017-021077
|View full text |Cite
|
Sign up to set email alerts
|

Binge drinking and associated factors among school students: a cross-sectional study in Zhejiang Province, China

Abstract: ObjectiveTo investigate the prevalence and correlating factors of binge drinking among middle and high school students in Zhejiang Province, China.MethodsWe performed a cross-sectional study using data from a school-based survey. A total of 23 543 (response rate=97.5%) eligible adolescents from 442 different schools (including middle schools, academic high schools and vocational high schools) were asked to fill in an anonymous self-administered behaviour questionnaire between April and May 2017. Multivariable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 59 publications
3
22
1
3
Order By: Relevance
“…People who experience feelings of hopelessness tend to harbour negative expectations about future life events and are more likely to experience depressive disorders or depend on substances like benzodiazepines, opiates, and alcohol [36]. Academic stress, the pressure to succeed, and peer competition may cause university students to relieve their stress by consuming alcohol [37]. Therefore, counselling centres in universities must be more proactive and help students who exhibit the symptoms of depression or experience feelings of hopelessness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People who experience feelings of hopelessness tend to harbour negative expectations about future life events and are more likely to experience depressive disorders or depend on substances like benzodiazepines, opiates, and alcohol [36]. Academic stress, the pressure to succeed, and peer competition may cause university students to relieve their stress by consuming alcohol [37]. Therefore, counselling centres in universities must be more proactive and help students who exhibit the symptoms of depression or experience feelings of hopelessness.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that students who smoked in the previous 30 days before the study were seven times more likely to consume alcohol than their non-smoking counterparts. Cigarette smoking during youth is strongly linked to subsequent alcohol use and abuse [6,20,[37][38][39][40]. A systematic review also concluded that a higher quantity and frequency of alcohol consumption was associated with a higher prevalence of tobacco smoking among European university students [41].…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of binge drinking among countries is complicated due to the differences in the methodology, drinking cultures, drink sizes, and other definitions as well as cultural differences observed 33 . The high rates found for alcohol consumption among adolescents represent a significant public health concern due to the possibilities of health damage in adolescents and the possibility of a problematic consumption in adult life 4,5,6,7,34 . Our findings show positive association between mothers that consume alcohol and binge drinking among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The last national drug survey revealed that 43.6% of Brazilian adolescents between 13 to 15 years old and 65.3% between 16 to 18 reported having consumed alcoholic beverages in the last year 3 . Violence, poor school performance, unprotected sex and drug use are multiple risk behaviors associated with this practice 4,5,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies exploring predictors related to heavy drinking among adolescents in various countries have identified a number of predictors, including differences by gender (Iwamoto et al, 2016), school grade (Chung & Joung, 2013;Larsen et al, 2017), bullying victimization (Wang et al, 2018), depression (Lamis, Ballard, May, & Dvorak, 2016), sleep quality (Hasler et al, 2017), exercise (Chung & Joung, 2018), current cigarette smoking (Chung & Joung, 2013), and sexual experience (Wang et al, 2018). Although these demographic characteristics and health and risk behaviors are often related or co-occurring, most of the preceding studies have studied only one concept, or have been studied only in the adolescents of one country (Chung & Joung, 2013), or have been conducted in other countries, such as US (Chung & Joung, 2018;Iwamoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%